The Effect of Motivation, Leadership and Discipline on Employee Performance: The Case of Population and Civil Registration Office of Palembang City - Angriani, Disti Yigi; Moelyati, Trisniarty Adjeng; Choiriyah, Choiriyah (International Journal of Marketing & Human Resource Research, 2025)
This study aims to determine 1) the influence of work motivation, leadership, and work discipline on employee performance at the Population and Civil Registration Service of Palembang City. 2) The influence of work motivation on employee performance at the Population and Civil Registration Service of Palembang City. 3) The Influence of Leadership on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 4) The Influence of Work Discipline on the Performance of Employees of the Population and Civil Registration Service of Palembang City. This type of research is Associative. The variables used by researchers include Work Motivation, Leadership, Work Discipline, and Performance. The population of this study consisted of all Employees of the Population and Civil Registration Service of Palembang City, and the sample size in the study was 101 employees. The sampling technique used was Proportionate Stratified Random Sampling. The data used in this study are primary data collected through a questionnaire. The data analysis technique used is multiple linear regression. The results of this study indicate that: 1) Work Motivation, Leadership, and Work Discipline have a significant effect on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 2) Work Motivation has a significant effect on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 3) Leadership has a significant influence on the performance of employees at the Palembang City Population and Civil Registration Service. 4) Work discipline has a significant influence on the performance of employees at the Palembang City Population and Civil Registration Service.